Decision Making With an Alternative Mindset in an Online Shopping Environment: Identifying User Intentions Toward Facebook-Commerce - Wang, Jian; Shahzad, Fakhar; Khan, Imran; Siyal, Abdul Waheed (Frontiers in Psychology, 2022)
Considering the current global trend in the digital economy, Facebook commerce (f-commerce) is an indispensable component of today’s digital commerce. The purpose of this research is to test the proposed model in order to validate current theories that evaluate the relationships between online trust and customer f-commerce usage intentions. It has also been proposed to improve usage intention by integrating the relationship between perceived value and trust in electronic commerce. The data was gathered using a structured questionnaire and analyzed with structural equation modeling (n=435). In this study, gender has been discussed as a moderating factor. The findings describe the positive relationships that exist between antecedents of trust and user intentions towards f-commerce. Furthermore, according to the findings of the study, females are more concerned than males about developing their intentions to utilize f-commerce for online shopping. Theoretical and practical implications are also presented in this study.